(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2021)
The complexity of the forest ecosystem is pervasive at ecological, socio-economic, socio-politic, and legislative levels; as a result, forest engineers’ practices are very complex. Previous studies on Syrian forestry sector, such as that of Cheikho (2009) and Martini (2009), have mentioned that Syrian forestry sector staffs find difficulties in practicing their career; within this context and seeing the actual degraded situation of Syrian natural forests, Syrian forestry educational institutions outputs could represent a legitimate discussing subject with Syrian forestry staffs. Along with this framework, in-service forest engineers have been interviewed to discuss professional requirements for being a well-trained forest engineer. This research tries to identify the aptness level of Syrian forestry educational institutions towards the real practice of their career. The targeted sample of this research consisted of twenty-one in-service Syrian forest engineers; Data were collected through carrying out semi-directive anonymous written interviews with them. According to a specific categorization system, the compilation of data has been submitted into a content analysis to find answers to this research problematic and questions. According to this research outputs, several subjects were perceived as slightly undertaken by forestry educational institutions and need to be enhanced; different levels of related values were identified. Accordingly, different institutional, job-related and educational interpretations have been made to discuss the aptness level of the Syrian forestry educational system towards the professional forestry praxis complexity.